The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/aob/mcq093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light on direct and indirect defences against herbivores of young plants of Mallotus japonicus demonstrate a trade-off between two indirect defence traits

Abstract: These results suggest that direct defence traits function regardless of light conditions, but light conditions affected the development of indirect defence traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Yamawo & Hada (2010) reported that the increase in EFN size and the decrease in food bodies occurred under high light conditions in young M. japonicus plants. Moreover, Yamawo, Hada & Suzuki (2012) and Yamawo et al (2012a) demonstrated that, in high soil nutrient and high moisture conditions, young M. japonicus increased EFNs and EF-nectar volume and decreased the densities of trichomes and pellucid dots.…”
Section: Introductionmentioning
confidence: 98%
“…Yamawo & Hada (2010) reported that the increase in EFN size and the decrease in food bodies occurred under high light conditions in young M. japonicus plants. Moreover, Yamawo, Hada & Suzuki (2012) and Yamawo et al (2012a) demonstrated that, in high soil nutrient and high moisture conditions, young M. japonicus increased EFNs and EF-nectar volume and decreased the densities of trichomes and pellucid dots.…”
Section: Introductionmentioning
confidence: 98%
“…For example, in light-rich and nutrient-poor conditions plants are expected to invest in carbon-based defenses, while in shaded but nutrient-rich conditions plants should invest more heavily in nitrogen-based defenses (Lerdau & Coley, 2002). Yamawo and Hada (2010) found that light intensity affected the trade-off between two indirect defenses in Mallotus japonicus. In low light conditions, both the size and the productivity of EFNs were reduced, but the production of pearl bodies was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Extrafloral nectar production has been observed to increase in response to high light intensity (Yamawo &Hada 2010, Jones andKoptur 2015b). Furthermore the induction of EFN production, either through treatment with jasmonic acid (Radhika et al 2010) or through leaf damage , has been found to be dependent on , Lange et al 2013.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations